(untitled) (Research, Society and Development, 2023)
During vaginal delivery, lacerations and episiotomy can occur due to reduced flexibility of the perineal muscles during pregnancy. The muscle stretching resulting from perineal massage can prevent injuries to the perineum. Therefore, the aim was to analyze the effectiveness of perineal massage in preventing lacerations during vaginal delivery. This is an integrative literature review, and the search was conducted in the Bireme, PubMed, PEDro, and Google Scholar databases, where articles published from 2012 to 2022 were selected. After careful reading, four articles were chosen to compose the study sample. Among the results found, perineal massage performed from the 30th or 36th week of gestation helps prevent injuries and pelvic floor dysfunctions. Thus, prenatal perineal massage increases the likelihood of an intact perineum, reduces the incidence of episiotomy and perineal lacerations and its degrees of involvement, shortens the duration of the second stage of labor, promotes the healing of perineal wounds, reduces perineal pain in 15 days after delivery, and may minimize the chances of developing flatulence incontinence and increase the strength of pelvic floor muscles.